Application of a new cyclic guanidinium ionic liquid on dye-sensitized solar cells (DSCs) - Li, Dongmei (Langmuir : the ACS journal of surfaces and colloids, 2009)
A new cyclic guanidinium ionic liquid OGI (1,3-dimethyl-2-N''-methyl-N''-octylimidazoguanidinium iodide) has been used as a quasi-solid-state electrolyte for dye-sensitized solar cells (DSCs), and 6.38% conversion efficiency was achieved at AM 1.5 simulated sunlight (9.81 mW cm(-2)). Further gelation with SiO2 nanoparticles afforded the solid-state electrolyte, which presented overall conversion efficiency of 5.85%. The diffusion properties of these OGI-based electrolytes were investigated. In the meantime, the optimal structure and ion-pairing interaction in OGI have been proposed by density functional theoretical calculation (DFT) at the B3LYP/6-21G(d,p) level. In view of the experimental and theoretical calculation results, it is suggested that high asymmetry and good charge delocalization of the cyclic guanidinium cation can well restrain the recombination reaction between the injected electrons in the TiO2 conduction band and I3- ions through its flexible hydrocarbon group, thus giving relatively high efficiency